<tex Notation="TeX">$\hbox{Er}^{3+}$</tex> and <tex Notation="TeX">$\hbox{Ce}^{3+}$</tex> Codoped Tellurite Optical Fiber for Lasers and Amplifiers in the Near-Infrared Wavelength Region: Fabrication, Optical Characterization, and Prospects - J. Lousteau (IEEE Photonics Journal, 2012)
A tellurite optical fiber doped with Er3+ and Ce3+ ions was designed and fabricated with the aim of assessing its suitability as laser and optical amplifier operating at 1550 nm, compatible with silica fiber standard dimensions. High-quality optical fibers, with an attenuation loss of 1.0 dB/m at 1320 nm, were obtained featuring a 6-μm diameter core. A fiber laser emitting at 1550 nm upon pumping at 976 nm and a fiber amplifier characterized by signal amplification of 8 dB for a length of 10 cm were demonstrated.